Analysis of the anti-cancer effect of ethyl-p-methoxycinnamate extracted cekur (Kaempferia galanga) on cancer cell lines with wild-type and null p53 - Ichwan, Solachuddin J. A.; Sazeli, Syahirah; Lestari, Widya (Kulliyyah of Dentistry, International Islamic University Malaysia, 2020)
This study aimed to examine the in-vitro anti-cancer potential of ethyl-p-methoxycinnamate (EPMC), the major constituent of Kaempferia galanga (K. galanga) in selected human lung adenocarcinoma cells line A549 (p53 wild-type) and H1299 (p53 null). The involvement of p53 pathway in the anti-cancer effect of EPMC on selected cells was determined using MTT assay and Real-time PCR. The MTT results show that EPMC induces cytotoxicity in a dose- dependent manner in A549 cancer cell lines containing the p53 wild-type gene. Meanwhile, our RT-PCR results indicate that the apoptotic activity of EPMC does not involve the p53 pathway. Overall, these results indicate that EPMC compounds of K. galanga stimulates in vitro cytotoxic and apoptotic activity unrelated to the p53 pathway.